Linker Dependence of Avidity in Multivalent Interactions Between Disordered Proteins. Issue 24 (6th December 2019) - Sørensen, Charlotte S.; Jendroszek, Agnieszka; Kjaergaard, Magnus
Abstract: Multidomain proteins often interact through several independent binding sites connected by disordered linkers. The architecture of such linkers affects avidity by modulating the effective concentration of intramolecular binding. The linker dependence of avidity has been estimated theoretically using simple physical models, but such models have not been tested experimentally because the effective concentrations could not be measured directly. We have developed a model system for bivalent protein interactions connected by disordered linkers, where the effective concentration can be measured using a competition experiment. We characterized the bivalent protein interactions kinetically and thermodynamically for a variety of linker lengths and interaction strengths. In total, this allowed us to critically assess the existing theoretical models of avidity in disordered, multivalent interactions. As expected, the onset of avidity occurs when the effective concentration reached the dissociation constant of the weakest interaction. Avidity decreased monotonously with linker length, but only by a third of what is predicted by theoretical models. We suggest that the length dependence of avidity is attenuated by compensating mechanisms such as linker interactions or entanglement. The direct role of linkers in avidity suggests they provide a generic mechanism for allosteric regulation of disordered, multivalent proteins. Graphical abstract: Image 1 Highlights: Intrinsically disordered linkers control avidity in multivalent protein interactions. Measurement of effective concentrations allows evaluation of theoretical models. Avidity decreases with disordered linker length, but less than predicted. Linker-linker interactions undermine models assuming passive protein linkers.